Investigating the efficacy of hydrogen peroxide agaisnt isolated environmental Escherichia coli strains - Giddey, Kirsten Francis (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc Food Sc)--Stellenbosch University, 2015.